Relationship of Contraceptive Use Depo Provera with The Side Effects On Acceptance in Nulle Health Center - Cangdra, Maria Iknasia Natasya; Ragaletha, Tadeus A; Sir, Amelya Betsalonia (Faculty of Public Health, Nusa Cendana University, 2020)
Contraception is an effort to prevent the onsany of pregnancy that is temporary and can be permanent. One of the contraceptive methods that is in demand by the public is the hormonal contraceptive method, namely the injectable contraceptive Depo Provera. Hormonal contraceptive methods are considered one method with high effectiveness, but on the other hand hormonal contraceptives especially those containing progesterone have some side effects such as menstrual cycle disorders, spotting, increased blood pressure and weight gain. This study aims to find out the relationship between the use of injectable contraceptive Depo Provera with the occurrence of side effects on the acceptance in Nulle publick health center South Central Timor Regency in 2020. This type of research is quantitative research using a cross sectional study approach. The sample in this study was 95 acceptances spread across 8 villages that became the working area of Nulle Health Center. The data analysis used is univariate analysis and bivariate analysis using Chi-square test. The characteristics of the majority of respondents aged 21-30 years and 31-40 years were 42.9%, not working 55.6%, high school education 54.0% and parity 1-2 people as much as 49.2%. The results of the data analysis showed there is a relationship between the use of injectable contraceptive Depo Provera with side effects in the form of menstrual cycle disorders (ρ-value = 0.004), spotting (ρ-value = 0.006) and increase in weight (ρ-value = 0.010) while unrelated side effects are an increase in blood pressure (ρ-value = 0.423). Advice for health officials especially in the field of maternal and child health and family planning to increase the frequency of counseling/information to acceptors, especially injectable contraceptive acceptors Depo Provera regarding the side effects of contraceptive use and other factors that can influence the onsling of such side effects by utilizing health promotion media, so that the acceptor can have a good information/understanding of the contraceptive used.